Competitive Advantage as Role Moderation Between System-Driven Performance and Economic Performance - Dirvi Surya Abbas; Daniel Rahandri; Imas Kismanah; Anita Ardiyanti (Quantitative Economics and Management Studies, 2022)
This paper aims to determine the relationship between environmental performance, corporate image, corporate social performance on economic performance by including competitive advantage as a moderator, as well as to describe why and how it is important to carry out corporate care for the environment by companies. This study also aims to expand the topic of discussion by including more variables related to aspects that affect company performance. The population of this study includes all manufacturing companies listed on the Indonesia Stock Exchange in the 2014-2018 Period. The sampling technique used the purposive sampling technique. Based on predetermined criteria obtained 11 companies. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analytical method used is panel data logistic regression analysis. This paper provides an empirical view of how environmental factors greatly affect the company's performance. This shows that the increase in good company performance generally comes from companies that pay attention to corporate social responsibility, so that they can have an advantage in competition in the market. Based on the research approach method used, this is a weakness of this study because this research cannot be generalized. It is hoped that future researchers will be able to explore the proportions of other variables that can be used in further research. These results support the legitimacy theory; one of the arguments (O’Donovan 2002) states that in the view of legitimacy, the relationship between profitability and the level of social performance is when the company has a high level of profit, the company considers it unnecessary to report things that can interfere with information. Consumers who are increasingly aware of environmental issues will look for environmentally friendly products. As a follow-up impact, the company will look for suppliers who can solve ecological problems; this will affect increasing the selling power of products or services and can improve the company's economic performance. This paper fulfills the identified need to study how environmental performance supports business excellence thereby improving company performance